SEASONAL OCCURRENCE AND SITE SELECTION OF LAMPROGLENA PULCHELLA VON NORDMANN, 1832 (COPEPODA, LERNAEIDAE) ON THE GILLS OF RUDD, SCARDINIUS ERYTHROPHTHALMUS (PISCES, CYPRINIDAE) - (:unkn) unknown (BRILL ACADEMIC PUBLISHERS, 2012)
The crustacean ectoparasite, Lamproglena pulchella Von Nordmann, 1832 (Copepoda, Lernaeidae) is found attached to the gill filaments of rudd, Scardinius erythrophthalmus (Linnaeus, 1758). During the present study, performed between March 2009 and February 2010 at monthly intervals at Lake Sapanca, Turkey, a total of 128 specimens of S. eryththrophthalmus were examined. Of these, 88 (68.8%) were infected by L. pulchella, which totalled 251 in number, with a mean intensity [mean number of parasites per infected fish] of 2.85 and a mean abundance [mean number of parasites calculated over all fish sampled] of 1.96 individuals. There was no distinct seasonality in the occurrence of L. pulchella throughout the study period. The maximum mean abundance of the infection was recorded as 2.84 individuals in July. The prevalence of L. pulchella increased with fish body size. The maximum intensity of the infection was 12 specimens of L. pulchella in July on a single fish. The branchial distribution of L. pulchella was studied and no preference was found in the distribution of the parasite between the gill arches on the left and right side. Gill arches II and III, medial segments, posterior hemibranches, and inner surface of the hemibranches were preferred by L. pulchella.
Keywords: ECOLOGY; FISH; FAMILY; RIVERS